GAPS AND CHALLENGES OF CANCER CARE IN A MULTIETHNIC POPULATION IN SARAWAK, BORNEO - Melissa Lim, Siaw Han; Voon, Pei Jye; Adibah, Ali; Fitri Suraya, Mohamad; Jong, Lin Lin; Chew, Lee Ping; Mohamad Adam, Bujang; Yolanda Sydney, Augustin; Cheng, Yuong Kang (Springer Nature, 2024)
The state of Sarawak on the island of Borneo, East Malaysia, in working towards developing and strengthening cancer services must focus on the comprehensive needs of cancer patients by taking into account the psycho-social, cultural and spiritual aspects of Sarawak’s multiethnic, multi-cultural population.